Regional financial integration, financial development and industrial sector growth in ECOWAS: Does institution matter? - Onyebuchi Iwegbu; Kainu Justine; Leonardo Chaves Borges Cardoso (Cogent Economics & Finance, 2022)
Regional economies seek to promote growth through industrialisation and literature suggests that developing the financial system, integrating the financial system within a sound institutional framework can promote industrial output. This study fills the gap by examining the impact of financial development and regional financial integration on ECOWAS' industrial sector. This study assesses whether regional financial integration and financial development have a stronger effect on the growth of the industrial sector of ECOWAS member countries that have high level of institutional quality than it does in countries with lower level. Major findings from the study reveals that deepening regional financial integration can only enhance the industrial output of ECOWAS member countries that has sound institutional quality framework; this is important and is a strong enhancing factor for member countries experiencing low industrial sector output. Credit to the private sector alone both for countries with low industrial output and countries with high industrial output does not improve the level of industrial performance. However, for countries that have low industrial output with a stronger institutional quality framework, increases in credit to the private sector will increase the level of industrial output compared to countries with a higher level of industrial output. Increasing the level of money in circulation alone does not improve industrial sector performance; the quantum channeled as credit to the private sector does. An improved institutional framework must be set in place together with an enhanced flow of credit to the private sector in ECOWAS.
Keywords: E44; F36; O14; O16; O43; 330; Regional financial integration; Financial development; Industrial sector growth; Institutional quality; ECOWAS